Differences between the effects of water Naftussya from fields of Truskavets' and Pomyarky on the parameters of the EEG, HRV, immunity and metabolism - Nadiya O Sydoruk; Walery Zukow (Kazimierz Wielki University, 2019)
Background. In previous studies involving subjects of both sexes with dysfunction of the neuroendocrine-immune complex, we found that the weekly use of Naftussya as Truskavets' and Pomyarky deposits generally has the same effect on its parameters.The purpose of this study is to identify the differences between the effects of water of these deposits. Material and research methods. Observations were conducted with the participation of 22 volunteers with a clinical diagnosis chronic pyelonephritis with dysfunction of the neuroendocrine-immune complex and metabolism. At first, they collected a daily urine, which determined the content of electrolytes and nitrogen metabolites, and then in the morning they started taking samples of capillary and venous blood for biochemical, hormonal and immune assays, as well as registering the HRV and EEG. After the initial survey, 10 volunteers spent 7 days drinking water Naftussya from the Pomyarky (NP) deposit, while the remaining 12 from Truskavets deposit (NT) (250 ml three times a day), after which the above tests repeated. Results. The use of NP does not affect the symmetrical theta-and delta-rhythms, as well as causes the right asymmetry of the alpha-rhythm, whereas NT causes the left-hand asymmetry of all three rhythms. Increased asymmetry of alpha-rhythm and amplitude of delta-rhythm under the influence of NP decreases to normal, whereas NT causes even more deviation of these parameters from the norm. The use of NP reduces both the normal spectral power (SP) of VLF band of HRV and the increased SP of LF band without affecting the normal SP of HF band. Instead, NT increases the SP of LF and HF bands without affecting the VLF band. The described differences in neurotropic effects are accompanied by a more pronounced increase in blood levels of active T-lymphocytes and T-killers and more pronounced stimulation of NP intensity of phagocytosis by neutrophils of Staph. aureus and E. coli, as well as the activity and completeness of phagocytosis the latter's. This leads to a somewhat more pronounced reduction of bacteriuria. Conclusion. The revealed differences, apparently, are due to differences in the composition of organic substances and autochthonous microflora.